DEVELOPMENT OF PROFESSIONALLY ORIENTED PHONETIC COMPETENCE OF PRE-SERVICE TEACHERS IN THE COURSE OF FOREIGN LANGUAGE CLASSES - Zenya, L.; Roman, S.; Kolominova, O. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The problem of professionally oriented phonetic competence of pre-service teachers in the course of foreign language classes and classes of Practical Phonetics in a foreign language higher educational institution of a bachelor degree level is investigated. The need for further improvements of the given competence in the light of increased requirements towards the national system of professional foreign language pre-service teachers training of potentially top professionals in the current intercultural foreign language educational environment has been emphasized. Consequently, the essence and components of the competence i.e. phonetic skills, knowledge and awareness have been specified. Specific peculiarities of phonetic competence compared against other linguistic competencies have been defined, especially it sensitivity to interlanguage interference and its ability for linguistic fossilization. Conceptual basics of the proprietary methodology of professionally oriented foreign language competence are highlighted. Moreover, some examples of professionally oriented tasks, elaborated by the authors in compliance with the requirements for teaching materials selection and teaching process planning of foreign language classes and Practical Phonetics are provided. _______________ References • Bory`sko N. F. Osobly`vosti formuvannya fonety`chnoyi kompetenciyi v umovax integrovanogo navchannya IM u movnomu VNZ // Metody`ka formuvannya mizhkul`turnoyi inshomovnoyi komunikaty`vnoyi kompetenciyi: kurs lekcij: (navch.-metod. posibny`k: dlya stud. movny`x specz. osv. -kvalif. rivnya «magistr») / Bigy`ch O. B., Bory`sko N. F., Borecz`ka G. E. ta in. / za red. S. Yu. Nikolayevoyi. – Ky`yiv, 2011. – S. 107-140. • Bory`sko N. F. Metody`ka formuvannya inshomovnoyi fonety`chnoyi kompetentnosti // Metody`ka navchannya inozemny`x mov i kul`tur: teoriya i prakty`ka: pidruchny`k dlya stud. klasy`chny`x, pedagogichny`x i lingvisty`chny`x universy`tetiv / Bigy`ch O. B., Bory`sko N. F., Borecz`ka G. E. ta in. / za zagal`n. red. S. Yu. Nikolayevoyi. – K.: Lenvit, 2013. – S. 192-195. • Gutny`k V. M. Formuvannya fonety`chnoyi kompetenciyi u majbutnix uchy`teliv nimecz`koyi movy` u komunikaty`vnomu vstupnomu korekty`vnomu kursi. Avtoref. dy`s. … kand. ped. nauk – 13.00.02. – K., 2017. – 24 s. • Doly`na A. V. Osobly`vosti procesu vdoskonalennya fonety`chnoyi kompetenciyi majbutnix uchy`teliv inozemny`x mov // Yakist` vy`shhoyi movnoyi osvity`: shlyaxy` vdoskonalennya organizaciyi i provedennya pedagogichnoyi prakty`ky` studentiv-filologiv. Materialy` III mizhnarodnoyi naukovo-prakty`chnoyi konferenciyi / za red. O. V. Rafiyenko. – Gorlivka: vy`davny`cztvo GDPIIM, 2009. – S. 230-233. • Zadorozhna I. P. Vy`mogy` do volodinnya lingvisty`chnoyu kompetenciyeyu majbutnimy` vchy`telyamy` anglijs`koyi movy` // Visny`k Ky`ivs`kogo nacional`nogo lingvisty`chnogo universy`tetu. Seriya: Pedagogika ta psy`xologiya. Vy`p. 17. – 2010. – S. 46-51. • Kolominova O. O., Roman S. V. Formuvannya anglomovnoyi fonety`chnoyi kompetentnosti u ditej molodshogo shkil`nogo viku / Kolominova O. O., Roman S. V. // Inozemni movy`. – 2006. – # 4. – S. 30-37. • Metody`ka navchannya inozemny`x mov i kul`tur: teoriya i prakty`ka: pidruchny`k dlya stud. klasy`chny`x, pedagogichny`x i lingvisty`chny`x universy`tetiv / Bigy`ch O. B., Bory`sko N. F., Borecz`ka G. E. ta in. / za zagal`n. red. S. Yu. Nikolayevoyi. – K.: Lenvit, 2013. – 590 s. • Nikolayeva S. Yu. Mizhkul`turna inshomovna osvita v Ukrayini: klyuchovi problemy` / S. Yu. Nikolayeva // Inozemni movy`. – 2016. – # 2. – S. 3-9. • Perlova V. V. Profesijno oriyentovane zanyattya z prakty`chnoyi fonety`ky` anglijs`koyi movy` u pedagogichnomu VNZ / V. V. Perlova // Inozemni movy`. – 2004. – # 2 – S. 23–27. • Perlova V. V. Metody`ka formuvannya u majbutnix uchy`teliv anglijs`koyi movy` profesijno oriyentovany`x sluxovy`movny`x navy`chok: Avtoref. dy`s. … kand. ped. nauk – 13.00.02. – K., 2007. – 24 s. • Red`ko V. G. Konstruyuvannya zmistu shkil`ny`x pidruchny`kiv z inozemny`x mov: teoriya i prakty`ka: monografiya / V. G. Red`ko. – K.: Pedagogichna dumka, 2017. – 628 s. • Roman S. V., Kolominova O. O., Chekal` G. S. Navchal`no-metody`chny`j kompleks “Wonderland” : Kny`zhka dlya vchy`telya / S. V. Roman, O. O. Kolominova, G. S. Chekal`. – 3-ye vy`d. dopov. – K. : Lenvit, 2000. – S. 135-136. • Roman S. V. Metody`ka navchannya anglijs`koyi movy` u pochatkovij shkoli:. [navchal`ny`j posibny`k] / S. V. Roman. – K. : Lenvit, 2009. – 216 s. • Roman S. V., Zyenya L. Ya. Teorety`ko-metody`chni zasady` ukladannya i vdoskonalennya navchal`ny`x program filologichnogo profilyu v konteksti onovlennya zmistu vy`shhoyi movnoyi osvity`: navch. posib. / S. V. Roman, L. Ya. Zyenya. – Gorlivka: vy`d.-vo GDPIIM, 2011. – 64 s. • Roman S. V., Zyenya L. Ya., Kolominova O. O. Teorety`ko-metody`chni zasady` ukladannya navchal`ny`x program z pidgotovky` vchy`teliv inozemny`x mov dlya vy`shhy`x pedagogichny`x navchal`ny`x zakladiv Ukrayiny` / S. V. Roman, L. Ya. Zyenya, O. O. Kolominova // Naukovi studiyi – XXI (kul`tura, osvita, antropocentry`chni parady`gmy` i suchasny`j svit) – Vy`pusk 5 (Tom 7) – K.: MILENIUM, 2015. – S. 107-128. • Kelly G. How to teach pronunciation. – Longman, 2004. – P. 154.